Wunderlich syndrome, inside out: A case report and brief literature review - Stojanović Mirjana; Adnađević Perica; Kosanović Tijana; Hajdarpašić Lejla; Đorđević Marjana (Srpski Arhiv za Celokupno Lekarstvo, 2025)
Introduction. Renal angiomyolipomas (AMLs) are neoplasms that can rarely rupture, causing hemorrhagic shock as the most serious complication. This pathological condition, (referring to AML) is classified as a benign tumor arising from the proliferation of epithelioid cells, consisting of fat tissue, blood vessels, and smooth muscle. Wunderlich syndrome describes a spontaneous, non-traumatic bleeding into the subcapsular or perirenal space. Most individuals with renal AML exhibit no symptoms and are often diagnosed incidentally; however, some may experience life-threatening complications such as rupture, hemorrhage, and circumstantial hypovolemic shock. Case outline. We describe a clinical presentation of AML with rupture in a female patient with a brief overview of other cases of AML in the literature. Female patient, 68 years old, admitted for examination due to sudden severe pain in the abdomen with propagation to the right lumbar region accompanied by nausea and fatigue. After a complete physical examination, an abdominal ultrasound, and a computed tomography scan, surgery was performed during which the right kidney was removed alongside the hematoma and the kidney envelopes, which were sent for histopathological analysis. The result of the histopathological analysis confirmed that it was AML. Conclusion. AMLs are benign neoplasms with potentially serious complications. The most serious complication of AML is rupture, leading to retroperitoneal hemorrhage, with tumor size being a significant risk factor. Considering the clinical importance of this potential complication, it is important to establish a swift and accurate radiological diagnosis, with the aim of timely therapeutic intervention and reduction of potential additional complications.